Laryngeal carcinoma presented with thyroid mass symptoms: The importance of early onset hoarseness and absent of laryngeal crepitus - Chew, Chuen Shiun; Mohamad, Irfan; Nik Hassan, Nik Fariza Husna; Ramasundram, Shankar; Mazlan, Mohd Zulfakar (Elsevier, 2017)
Presentation of stridor with a marked anterior neck swelling is always presumed as thyroid mass compressing on the airway. However, a history of progressive hoarseness prior to the stridor should be taken into consideration as the airway obstruction might be due to intraluminal airway compression. We report an atypical presentation of laryngeal cancer with anterior neck swelling, which moved with swallowing, mimicking a thyroid tumour which cause delay of the management.